2016
DOI: 10.1097/md.0000000000004543
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different dipeptidyl peptidase-4 (DPP-4) inhibitors on metabolic parameters in patients with type 2 diabetes undergoing dialysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…While there were no significant differences in the relationship between acute glucose lowering and plasma DPP‐4 inhibition for the DPP‐4 inhibitors investigated in our study, the methods used were not designed to rule out potentially small differences between these agents. The observation that different DPP4 inhibitors have similar glucose‐lowering efficacy in the clinic has been reported in the literature (eg, Park et al) although there is a paucity of directly comparative studies. Moreover, despite the fact that soluble DPP‐4 in mixed venous plasma comprises only a small part of the total pool of DPP‐4 in the body, the majority being membrane bound, the extent of inhibition of the plasma enzyme does appear to predict glucose‐lowering activity well in mice as well as in humans …”
Section: Discussionmentioning
confidence: 84%
“…While there were no significant differences in the relationship between acute glucose lowering and plasma DPP‐4 inhibition for the DPP‐4 inhibitors investigated in our study, the methods used were not designed to rule out potentially small differences between these agents. The observation that different DPP4 inhibitors have similar glucose‐lowering efficacy in the clinic has been reported in the literature (eg, Park et al) although there is a paucity of directly comparative studies. Moreover, despite the fact that soluble DPP‐4 in mixed venous plasma comprises only a small part of the total pool of DPP‐4 in the body, the majority being membrane bound, the extent of inhibition of the plasma enzyme does appear to predict glucose‐lowering activity well in mice as well as in humans …”
Section: Discussionmentioning
confidence: 84%
“…These drugs, which were approved for clinical use in 2006, provide an effective therapeutic option without the drawback of inducing hypoglycemia and can be used safely in patients receiving dialysis. DPP-4 inhibitor use was found to significantly improve the HbA1c level and hyperglycemia in patients receiving PD [33,34]. Glycemic control is known to influence clinical outcomes, including mortality, in patients with chronic kidney disease who are and are not receiving dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of DPP-4 inhibitors' effects on lipid metabolism parameters are diverse and inconclusive [2]. Park et al reported a significant increase in HDL concentration in patients with 12-week administration of sitagliptin or linagliptin, and showed a decreasing trend in TC, TG, and LD in patients with 12-week administration of sitagliptin, vildagliptin, or linagliptin [19]. Kubota et al reported that administration of sitagliptin significantly decreased TC and LDL concentrations, and tended to decrease HDL concentration in patients with type 2 DM, up to 12 weeks [9].…”
Section: Discussionmentioning
confidence: 99%